Prevalence of chronic musculoskeletal pain among active and retired military personnel: a systematic review protocol. Issue 2 (27th February 2021) - Reyes, Julian; Shaw, Lynn E.; Lund, Heidi; Heber, Alexandra; VanTil, Linda
ABSTRACT: Objective: The objective of this review is to assess the prevalence of musculoskeletal chronic pain among active and retired members of military forces and to characterize potential factors that could influence the frequency of musculoskeletal chronic pain. Introduction: Inherent to military occupations is a diverse source of occupational hazards that affect the well-being of individuals at any stage of their military career (active and retired). Chronic pain may result from the continuous exposure to physically demanding tasks and other risks. Moreover, chronic pain has been associated with other comorbidities, including mental health conditions. Inclusion criteria: Scientific papers in French or English reporting on chronic pain derived from a musculoskeletal cause in active and retired military personnel will be considered. There will be no restriction on participants' country, age, or length of service. Methods: The published literature will be identified by exploring biomedical, pharmacological, and physiology bibliographic databases. The unpublished literature will be located through the search of thesis and gray literature repositories. This review will follow the condition-context-population approach and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The extracted data will include any detail about the anatomic location, diagnosis, types of studies, and risk factors. The review will follow JBI methods of critical appraisal, data extraction, and data synthesis for reviews containing prevalence data. If enough evidence is found, meta-regression analysis will performed, otherwise a narrative review will be completed. Systematic review registration number: PROSPERO CRD42020153704